(untitled) (Global Journal of Computer Science and Technology, 2022)
Eye diseases usually cause blindness and visual impairment As per the statistics there are over 285 million visually impaired people living worldwide They come across many troubles in their daily life especially while navigating from one place to another on their own They often depend on others for help to satisfy their day-to-day needs So it is quite a challenging task to implement a technological solution to assist them Several technologies were developed for the assistance of visually impaired people One such attempt is that we would wish to make an Integrated Machine Learning System that allows the blind victims to identify and classify real-time objects generating voice feedback and distance Which also produces warnings whether they are very close or far away from the thing